Catchment & sewer network simulation model to benchmark control strategies within urban wastewater systems. (April 2016) - Saagi, Ramesh; Flores-Alsina, Xavier; Fu, Guangtao; Butler, David; Gernaey, Krist V.; Jeppsson, Ulf
Abstract: This paper aims at developing a benchmark simulation model to evaluate control strategies for the urban catchment and sewer network. Various modules describing wastewater generation in the catchment, its subsequent transport and storage in the sewer system are presented. Global/local overflow based evaluation criteria describing the cumulative and acute effects are presented. Simulation results show that the proposed set of models is capable of generating daily, weekly and seasonal variations as well as describing the effect of rain events on wastewater characteristics. Two sets of case studies explaining possible applications of the proposed model for evaluation of: 1) Control strategies; and, 2) System modifications, are provided. The proposed framework is specifically designed to allow for easy development and comparison of multiple control possibilities and integration with existing/standard wastewater treatment models (Activated Sludge Models) to finally promote integrated assessment of urban wastewater systems. Graphical abstract: Highlights: Plant-wide Benchmark simulation model is extended to include the catchment and sewer system. The extended model describes the generation and transport of wastewater. New evaluation criteria are defined for benchmarking control strategies/structural modifications. Case studies depicting the usefulness/application of the model are performed.